Evaluasi Kinerja Eksperimental Mekanisme Gateway-Polled Sequential Access (GPSA) pada Jaringan LoRa Multi-Node Single-hop untuk Aplikasi Internet of Things (IoT) - Ridho, Sahid; Dahlan, A Ahmad; Yustini, Yustini; Rusfandi, Rusfandi; Ferdiansyah, Ferdiansyah (Politeknik Negeri Lhokseumawe, 2025)
This study presents the development and experimental evaluation of a single-hop multi-node LoRa communication system implementing the Gateway-Polled Sequential Access (GPSA) mechanism. The proposed GPSA scheme is a simplified form of Time Division Multiple Access (TDMA), where the gateway acts as the central controller that sequentially triggers each node via a START command, ensuring collision-free communication. The system was tested in four communication scenarios (1–4 nodes) at distances of 10 m, 50 m, 100 m, and 200 m in an open-field environment using E22-900T22D LoRa modules, INA219 current sensors, and a microSD-based logging system. The evaluated parameters included Received Signal Strength Indicator (RSSI), Round Trip Time (RTT), Packet Delivery Ratio (PDR), and the energy consumption of both the gateway and nodes. Experimental results show that the RSSI decreased reasonably from −51 dBm to −82 dBm as distance increased, while RTT remained stable between 760–820 ms. The PDR consistently achieved 100% across all test scenarios, confirming the reliability of the sequential polling mechanism in avoiding transmission collisions. Node energy consumption remained stable at 16–18 mJ per communication cycle and was independent of distance, while gateway energy consumption increased proportionally with the number of active nodes. With a 7.4 V / 1100 mAh Li-Po battery, each node can operate continuously for approximately 17 days. Overall, the LoRa-GPSA system demonstrated high energy efficiency, communication stability, and straightforward implementation, making it an effective solution for medium-range IoT field applications